Gravitation, following the Prague inspiration
This is a festschrift celebrating the 60th birthday of Professor Jici Biak. The contributors are his former students who are working in the fields of general relativity, astrophysics, theoretical physics and cosmology. The articles present original results or survey those already published elsewhere. The subjects range from the motion of stars in galactic nuclei to quantum mechanics on a boundary, and include several hot topics of relativistic physics - cosmological perturbations, the repulsive cosmological constant, discs around black holes, and gravitational waves